Archbishop Pecham’s Register - Douie, Decima L. (Studies in church history, 1964)
Archbishop Pecham’s register is not only interesting as the first surviving Canterbury register, but also because an attempt has been made in it to abandon the older chronological arrangement for some sort of classification of documents in order to facilitate rapid consultation. The scheme adopted is unique among English registers, being that used by the Curia, for the letters are divided into ‘littere directe pape et cardinalibus,’ ‘littere regi,’ ‘littere episcopis’ and ‘littere communes.’ This order, however, is not rigidly followed, for there is a special section of’littere directe domino pape,’ and many letters to bishops are included among the ‘littere communes.’ Nevertheless, the arrangement was probably due to John of Bologna, the Italian notary brought by Pecham to England. To make consultation even easier, each leaf on which they occur has the heading ‘littere communes’ followed by the year of the archiepiscopate. There is also a rough sub-classification, not very systematically followed.